Labor Conflicts and Temporal Strategies: An Autoethnographic Analysis of the Summer Work and Travel Program (2023-2024) - Monge Alarcón, María Fernanda (2024)
This article aims to explore the labor challenges faced by Peruvian students in the Summer Work & Travel (SWT) program. Using an autoethnographic methodology, I analyze and reflect on my own experience as a participant in the SWT program, considering the conflicts faced by young participants and the strategies they develop in response to these situations. In this sense, I question the implications of SWT as an exchange program whose participants fulfill roles as temporary migrant workers.